2022
DOI: 10.3390/jcm11133814
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Conditions Related to Sarcopaenia among Older Persons Living in the Community

Abstract: (1) Background: In health care and in society at large, sarcopaenia is a disorder of major importance that can lead to disability and other negative health-related events. Our study aim is to determine the prevalence of sarcopaenia among older people attended in primary care and to analyse the factors associated with this age-related clinical condition; (2) Methods: A multicentre cross-sectional study was conducted of 333 community-dwelling Spanish adults aged 65 years or more. Sociodemographic, clinical, func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Psychiatric disorder was measured by six studies, with three studies reporting it as a significant risk factor. Two studies by Blanco-Reina et al 24,25 reported OR of 2.22 (95% CI 1.13-4.37) and 2.91 (95% CI 1.83-4.66), respectively, while another study by Berger et al 23 showed that patients with comorbid depression were more likely to receive PIM (51.6% vs 35.5% for those without comorbid depression; p < .01). Digestive disorder was reported as a risk factor by Berger et al 23 (43.0% vs 36.6% for those without the disorder; p = .04), while musculoskeletal disorder was reported as a risk factor by Fiss et al 35 (OR 4.20, 95% CI 1.10-16.01).…”
Section: Multimorbiditymentioning
confidence: 98%
See 1 more Smart Citation
“…Psychiatric disorder was measured by six studies, with three studies reporting it as a significant risk factor. Two studies by Blanco-Reina et al 24,25 reported OR of 2.22 (95% CI 1.13-4.37) and 2.91 (95% CI 1.83-4.66), respectively, while another study by Berger et al 23 showed that patients with comorbid depression were more likely to receive PIM (51.6% vs 35.5% for those without comorbid depression; p < .01). Digestive disorder was reported as a risk factor by Berger et al 23 (43.0% vs 36.6% for those without the disorder; p = .04), while musculoskeletal disorder was reported as a risk factor by Fiss et al 35 (OR 4.20, 95% CI 1.10-16.01).…”
Section: Multimorbiditymentioning
confidence: 98%
“…While it is not yet clear on why there are such associations, the literature has reported the links of these diseases to specific classes of drugs. For example, PIM in psychiatric disorders has been linked to the over-prescribing of psychotropic drugs such as antidepressant, sedatives (anxiolytics, hypnotics) and antipsychotic, [23][24][25]35,58,59 possibly due to the lack of prescribers' knowledge on the use of psychotropics. 60,61 Meanwhile, PIP in digestive disorders have been linked to the overuse of acid suppressing treatments such as proton pump inhibitors in the absence of clear clinical indications 62 ; PIMs in musculoskeletal disorders are linked to inappropriate use of analgesics such as opioid and non-steroidal antiinflammatory drugs 63,64 ; and PPO in cardiovascular disorders are linked to under-prescribing of aspirin, statin and angiotensin-converting enzyme inhibitor.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%